Overexpression of neuroserpin in larval and adult zebrafish shows different behavioral phenotypes. (25th September 2021) - Han, Sha; Zhang, Dongyang; Dong, Qiang; Wang, Xu; Wang, Liang
Highlights: An inducible neuroserpin overexpression zebrafish model is generated to study behavior in larval and adult zebrafish. Neuroserpin overexpression zebrafish larvae show decreased locomotion compared with wild type. Neuroserpin overexpression adult zebrafish is more anxious behavior than wild type. Abstract: Serpini1, which encodes neuroserpin, has been implicated in the development and maintenance of the nervous system. In this study, an inducible neuroserpin overexpression transgenic zebrafish was generated to investigate its role in different developmental stages. Neuroserpin overexpression was induced by doxycycline in larval and adult zebrafish respectively. Locomotion and thigmotaxis were recorded and analyzed using the ZebraBox high-throughput monitoring equipment and the ZebraLab software system. We find that Tg ( serpini1 ) (+DOX) zebrafish larvae are more hypoactive than their wild-type counterparts at 7 day-postfertilization and anxiety-like behavior is observed in Tg ( serpini1 ) (+DOX) adult zebrafish at 3 month-postfertilization. Furthermore, RNA-sequencing analysis reveals that neuroserpin overexpression affects neurodegeneration-related gene expression. In summary, we report that neuroserpin overexpression in larval and adult zebrafish shows different behavioral phenotypes.